Synthesis and characterization of heterostructure Pt/Bi2WO6 nanocomposites with enhanced photodegradation efficiency induced by visible radiation - Pinchujit, Soraya; Phuruangrat, Anukorn; Wannapop, Surangkana; Sakhon, Thawatchai; Kuntalue, Budsabong; Thongtem, Titipun; Thongtem, Somchai (Solid state sciences, 2022)
Bi2WO6 samples loaded with different weight contents of Pt were successfully synthesized by microwave-assisted deposition method. The as-synthesized Bi2WO6 and Pt/Bi2WO6 samples were analyzed by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, Raman spectrophotometry, scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV–visible diffuse reflectance spectroscopy (UV–vis DRS), photoluminescence (PL) spectroscopy, nitrogen adsorption/desorption isotherms measurement and X-ray photoelectron spectroscopy (XPS). The analytical results showed that metallic Pt nanoparticles with approximately size of 8–10 nm were well dispersed on thin orthorhombic Bi2WO6 nanoplates to form heterostructure Pt/Bi2WO6 nanocomposites. The Pt nanoparticles played the role in improving visible light harvest of the Bi2WO6 nanoplates. Their photocatalytic activities were evaluated through rhodamine B (RhB) degradation under visible radiation (λ ≥ 420 nm) of a xenon light source. The photodegradation efficiencies of pure Bi2WO6 and 10% Pt/Bi2WO6 samples induced by visible light within 180 min were respectively 35.33% and 98.09% caused by charge diffusion at the Pt/Bi2WO6 interface and surface plasmon resonance (SPR) effect of Pt nanoparticles. In this research, the reused 10% Pt/Bi2WO6 nanocomposites with excellent stability and high photo-resistance were the promising photocatalyst for environmental remediation. Schematic diagram for photocatalysis of heterostructure Pt/Bi2WO6 nanocomposites induced by visible radiation. [Display omitted] •Pt/Bi2WO6 nanocomposites as a type IV mesoporous material.•The nanocomposites with different Pt contents were studied for photocatalysis.•The promising material used for wastewater treatment.